EFECTO DEL ESTRADIOL EN EL PERIODO DE RECONOCIMIENTO MATERNAL DE LA PREÑEZ SOBRE LA SUPERVIVENCIA EMBRIONARIA EN ALPACAS - Chipayo G., Ysaac (2003)
The effect of oestradiol (E2 ) during the maternal recognition of pregnancy (9-11 days after ovulation) was studied in 44 alpacas that were >20 days after delivery. The alpacas were mated with an intact male (>15 minutes) and received 500 IU of hCG to induce ovulation. The females were divided in 3 groups: Group G1 (n=14) received 0.2 ml. i.m. of an A, D and E vitaminic complex on days 8 and 9 post-ovulation. Group G2 (n=15) received 200 mg of E2 and 0.2 ml i.m. of the vitamin complex (similar to G1 ) on days 8 and 9 post-ovulation. Group G3 (n=15) received 20 mg of progesterone and 0.2 ml i.m. of the same vitamin complex on day 9 post-ovulation. The females were confronted with a male to evaluate their sexual behavior (accept or denial) and then, transrectal ecography of the ovaries and uterus was conducted on days 2, 8, 13, 19, 27, 30 and 60 post-ovulation. Embryonic survival was higher in G2 (86.7%) at day 19 in comparison to G1 (57.1%, p<0.08), but without differences with G3 (73.3%). Follicular dinamics in alpacas with embryonic survival was different at day 2 (p<0.1) but not on day 8 relating to those animals with embrionic mortality. The size of the corpus luteum did not have statistical differences between the three groups but was smaller in those with embryonic mortality at day 13 (10.7 ± 1.6 vs. 13.3 ± 1.5, p<0.05) which would show that the luteolisis process began at day 13 in that group. These results suggest that failure in maternal recognition of pregnancy and subsequent embryo mortality were reduced by the oestradiol, and therefore, indicating that oestradiol plays an important role in the process of maternal recognition of pregnancy in alpacas.